"O exército dos mortos" : sentido do sacrifício e da transcendentalidade na militância revolucionária, caso do exército de libertação nacional (ELN) da Colômbia (2012)
ABSTRACT: In this article I discuss the strength of the religious in the identifiable constitution of the Colombian revolutionary guerrilla (ELN) national liberation army, arisen in 1964 and yet in force as an army struggle project. Although the ELN defines itself as an atheist organization that follow the Marxism-Leninism principles, the dead in combat of the priest Camilo Torres activated one of the germinal principles of the Christian traditions to the inner of the group: Jesus sacrifice by humanity, it is a message translated to the social fight and converted in straggle premise. This sacrifying vision will pass by the distinct contexts, practices, ways of expression and lectures from the elenos world that bind itself into a significant and structural element of the identity of the group.